Propuesta de estrategia metodológica para la formación del pensamiento crítico de los jóvenes del Taller Escuela San Patricio (TESPA) desde la perspectiva de Paulo - Alcoser, Tito (2012)
This project aims to contribute to the formation of critical thinking in the youth of St. Patrick School Workshop (PTSD) from the perspective of Paulo Freire and by methodological strategies. For this, the methodology used was documentary analysis of both educational theory and the information obtained in the in-depth interview was conducted for teachers, and the information obtained from students using the technique of focus groups. We analyzed a number of methods applied in PTSD. On the part of teachers, among the most representative, we have the method of direct observation, audio-visual-way motor-gnosis, the deductive inductive method of four stages, Holistic Approach, methodology kinesthetic, preventive system of Don Bosco, playful method, traditional methodologies.